Urban and Peri-urban Dairy Production System in Semi-arid Region of Uttar Pradesh - Singh, Amit (Indian Journal of Animal Production and Management, 2024)
Urban and peri-urban area are dairy intensive area which provides milk and milk products to the urban areas and thus help to generates regular income to these farmers. With rise in the urbanization the demands of milk and milk products is rising and farmers should be prepared the accelerating demands. The production of dairy animal is mostly influenced by feeding, management, health care and management practices with a clear understanding about scientific knowledge. Therefore, the efforts are made to assess the knowledge level of farmers and the factors affecting the dairy production in urban and peri-urban areas. This study was conducted purposively to assessing the Urban and Peri-urban Dairy production system in semi-arid region of Uttar Pradesh. The information on Urban and Peri-urban Dairy production system was collected using structured interview schedule from 120 households rearing cattle and buffalo from urban and peri-urban area. The results showed that majority of the respondents were having high dairy farming experience and buffalo was the preferred animal rather than cow. Majority of the farmers timely fed colostrum to newly born calves (97.50%) but the practice of feeding mineral mixture to animals is still the matter of concern. Majority of farmers were relying on natural service for breeding their bovines. Majority of farmers cleaned shed at regular interval to avoid infection and majority of them vaccinate their animals against one or the other diseases.